Are would-be authoritarians right? Democratic support and citizens' left-right self-placement in former left- and right- authoritarian countries. Issue 2 (17th February 2021) - de Leeuw, Sjifra E.; Rekker, Roderik; Azrout, Rachid; van Spanje, Joost H. P.
ABSTRACT: Conventional wisdom dictates that the more citizens lean towards either end of the ideological spectrum, the lower their support for democracy. The main model pitted against this "rigidity-of-the-extremes model" is the "rigidity-of-the-right model". This model assumes that rightist citizens are less supportive. This study proposes and empirically demonstrates the validity of an alternative model, which we call "the authoritarian legacy model". This model predicts that whether leftist or rightist citizens are less supportive of democracy depends on countries' experience with left- or right-authoritarianism. To evaluate its validity, we present a systematic comparative investigation of the relation between citizens' ideological and democratic beliefs, using European and World Values Survey data from 38 European countries ( N = 105, 495; 1994-2008). In line with this model, our analyses demonstrate that democratic support is lowest among leftist citizens in former left-authoritarian countries and among rightist citizens in former right-authoritarian countries. We find that this relation persists even among generations that grew up after authoritarian rule. These findings suggest that traditional ideological rigidity models are unsuitable for the study of citizens' democratic beliefs.